A CRITICAL APPRAISAL OF RESERVE BANK OF INDIA INITIATIVES IN COMBATING THE CONSEQUENCES OF COVID-19 LOCKDOWN - Dr. Nitin Pathak (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The paper studies the policy changes brought in by the banking regulator i.e, Reserve Bank of India in response to the challenges faced by MSME sector in particular and financial sector in general on account of halt in economic activity due to lockdown imposed on account of COVID-19 pandemic. This paper also focuses on the movement of funds inflows and outflows by foreign institutional investors in Indian capital markets in equity, debt and derivatives segments